Broadband abnormal reflection based on a metal-backed gradient index liquid slab: an alternative to metasurfaces. (18th May 2015) - Feng, Mingde; Tian, Xiaoyong; Wang, Jiafu; Yin, Ming; Qu, Shaobo; Li, Dichen
Abstract: We present an alternative method of introducing phase discontinuity, and demonstrate the design, fabrication and characterization of a thin abnormal-reflection slab using compound liquids in a sterolithography container. Normally incident electromagnetic waves penetrate into the gradient index slab and then are reflected by the metallic backing. Because gradient phase difference is produced on the thin slab surface, the propagation direction of the reflected beam is modulated. To obtain the phase gradient, we mix two liquids with different permittivities, which can realize a refraction index ranging from 1.6 6.5. To load and separate liquids with different refractive indexes, the sterolithography technique is used to fabricate the thin-walled container using photosensitive resin. We designed and fabricated a sample which has a 30° abnormal reflection angle under normal incidence with a thickness of 1/7 of the wavelength under 8.0 GHz. Broadband far-field patterns, as well as a near-field map at the working frequency, were simulated, theoretically discussed and experimentally measured. The results verify abnormal reflection of the sample. Compared with abnormal-reflection metasurfaces, the thin slab has a wider bandwidth (the relative bandwidth is 50%) and weaker polarization dependence.